A mixed-method approach of pre-cooling enhances high-intensity running performance in the heat - Xu, M.; Wu, Z.; Dong, Y.; Qu, C.; Xu, Y.; Qin, F.; Wang, Z.; Nassis, G. P.; Zhao, J. (Journal of Sports Science & Medicine, 2021)
We investigated whether single or combined methods of pre-cooling could affect high-intensity exercise performance in a hot environment. Seven male athletes were subjected to four experimental conditions for 30 min in a randomised order. The four experimental conditions were: 1) wearing a vest cooled to a temperature of 4 °C (Vest), 2) consuming a beverage cooled to a temperature of 4 °C (Beverage), 3) simultaneous usage of vest and consumption of beverage (Mix), and 4) the control trial without pre-cooling (CON). Following those experimental conditions, they exercised at a speed of 80% VO2max until exhaustion in the heat (38.1 ± 0.6 °C, 55.3 ± 0.3% RH). Heart rate (HR), rectal temperature (Tcore), skin temperature (Tskin), sweat loss (SL), urine specific gravity (USG), levels of sodium (Na+) and potassium (K+), rating of perceived exertion (RPE), thermal sensation (TS), and levels of blood lactic acid ([Bla]) were monitored. Performance was improved using the mixed pre-cooling strategy (648.43 ± 77.53 s, p = 0.016) compared to CON (509.14 ± 54.57 s). Tcore after pre-cooling was not different (Mix: 37.01 ± 0.27 °C, Vest: 37.19 ± 0.33 °C, Beverage: 37.03 ± 0.35 °C) in all cooling conditions compared to those of CON (37.31 ±0.29 °C). A similar Tcore values was achieved at exhaustion in all trials (from 38.10 °C to 39.00 °C). No difference in the level of USG was observed between the conditions. Our findings suggest that pre-cooling with a combination of cold vest usage and cold fluid intake can improve performance in the heat.